Familial Mediterranean Fever Is Associated With Increased Mortality After Kidney Transplantation—A 19 Years' Single Center Experience. Issue 10 (October 2017) - Green, Hefziba; Lichtenberg, Shelly; Rahamimov, Ruth; Livneh, Avi; Chagnac, Avry; Mor, Eytan; Rozen-Zvi, Benaya
Abstract : Background: Current data regarding the outcome of kidney transplantation in patients with familial Mediterranean fever (FMF) who reach end-stage renal disease (ESRD) due to reactive amyloidosis A (AA) are scarce and inconclusive. Methods: The outcomes of 20 patients with FMF and biopsy-proven AA amyloidosis that were transplanted between 1995 and 2014 were compared with 82 control patients (32 with diabetes mellitus and 50 with nondiabetic kidney disease). Major outcome data included overall patient and graft survivals. Results: During a mean overall follow-up of 116.6 ± 67.5 months 11 patients (55%) with FMF died versus 26 patients (31%) in the control group. Median time of death for patients with FMF was 61 months (range, 16-81) after transplantation. Estimated 5-year, 10-year, and actuarial 15-year overall patients survival rates were 73%, 45%, and 39%, respectively, for patients with FMF, versus 84%, 68% and 63%, respectively, for the control group ( P = 0.028). FMF was associated with more than twofold increased risk for death after transplantation, and with a threefold increased risk for hospitalization because of infections during the first year. Infections and cardiovascular disease were the cause of death in the majority of patients with FMF. Overall graft survival was similar between the groups. Recurrence of AA amyloidosis was diagnosed in 2 patients during the first year after transplantation. Conclusions: FMF is associated with increased risk of mortality after kidney transplantation. Abstract : Kidney transplant patients with familial Mediterranean fever (FMF) who reach end stage renal disease due to reactive amyloidosis A are associated with more than 2-fold increased risk for death after kidney transplantation and leading causes of death are Infections and CVD.